Utilization of Rice Washing Water to Enhance Growth and Fertility of Home Garden Plants - Paranita, Ekayana Sangkasari; Tatan Sukwika (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2025)
This community service program aims to educate the public about the potential of rice washing water as a nutrient-rich Liquid Organic Fertilizer (LOF), replacing chemical fertilizers that harm soil and the environment. Through participatory training, participants are taught fermentation techniques to convert household waste into LOF rich in carbohydrates, vitamins, and minerals. The program includes socialization on the dangers of chemical fertilizers, hands-on LOF production practices, and regular mentoring to optimize home gardens. Evaluation results show significant improvements in participants' understanding: the percentage of Strongly Agree responses regarding general LOF knowledge rose from 22% to 53%, and the ability to formulate LOF improved by 36%. Participants successfully utilized their home gardens to grow organic vegetables at lower costs and with healthier yields. This program not only reduces reliance on chemical fertilizers but also promotes household economies and environmental sustainability. Through a learning-by-doing approach, communities have become self-reliant in managing waste and implementing small-scale organic farming.